The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1161/strokeaha.111.000531
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With 28-Day Hospital Readmission After Stroke in Australia

Abstract: Background and Purpose-Understanding the factors that contribute to early readmission after discharge following stroke is limited. We aimed to describe the factors associated with 28-day readmission after hospitalization for stroke. Methods-Factors associated with readmission were classified from the medical record standardized audits of 50 to 100 consecutively admitted patients with stroke from 35 Australian hospitals during multiple time periods (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 21 publications
4
42
0
Order By: Relevance
“…Several studies have been undertaken to examine the frequency of readmissions within 30 days of discharge after stroke [13,27]. Evidence from these studies show that the frequency of hospital readmissions may vary from 6.5% to 24.3% [27]. The readmission rate in our study was comparable to what has been reported using Medicare data (12-14%) or single center studies (10%) [11].…”
Section: Journal Of Neurology and Neuroscience Issn 2171-6625supporting
confidence: 78%
See 2 more Smart Citations
“…Several studies have been undertaken to examine the frequency of readmissions within 30 days of discharge after stroke [13,27]. Evidence from these studies show that the frequency of hospital readmissions may vary from 6.5% to 24.3% [27]. The readmission rate in our study was comparable to what has been reported using Medicare data (12-14%) or single center studies (10%) [11].…”
Section: Journal Of Neurology and Neuroscience Issn 2171-6625supporting
confidence: 78%
“…The second important finding from our study is that the frequency of all-cause readmission in this study was 8.5% at 30 days and 18.5% at 90 days after discharge. Several studies have been undertaken to examine the frequency of readmissions within 30 days of discharge after stroke [13,27]. Evidence from these studies show that the frequency of hospital readmissions may vary from 6.5% to 24.3% [27].…”
Section: Journal Of Neurology and Neuroscience Issn 2171-6625mentioning
confidence: 99%
See 1 more Smart Citation
“…6,9 Furthermore, the few hospital-based studies have used different methodologies and have included only limited data on disease severity, hospital course, and outcomes. [10][11][12][13] A recent review of hospital standards for quality reporting of readmissions after stroke concluded that future work should focus on identifying risk factors at the patient level that are not typically or reliably included in administrative data sets. 14 Although identification of predictors for stroke readmission is important, many previously identified factors including age and initial stroke severity are nonmodifiable and thus provide limited opportunity for targeted interventions.…”
mentioning
confidence: 99%
“…Past research on the association between smoking status and readmission rates has produced equivocal results. [26][27][28][29][30][31][32][33][34] Many studies have examined commonly collected demographic variables. It has been reported that increasing age could potentially serve as a predictor of all-cause hospital readmissions, especially in patients over the age of 65.…”
Section: Discussionmentioning
confidence: 99%